Depression screening in patients with coronary heart disease: a narrative review of the current evidence = Depressionsscreening bei Patienten mit koronarer Herzkrankheit : ein narrativer Überblick über die aktuelle Evidenz - Kohlmann, Sebastian (Herz, 2024)
In view of the large and sometimes conflicting body of research, this narrative review summarizes the current evidence on depression screening in patients with coronary heart disease. Depression is a risk factor for development and progression of coronary heart disease. Consequently, many international cardiac guidelines recommend screening for depression in patients with coronary heart disease. However, the efficacy and implementation of these guidelines are debated due to the lack of empirical evidence supporting the benefits of routine depression screening. Studies conducted in cardiac routine care support this assumption: Patients with positive depression screens do not receive adequate follow-up care, which highlights gaps in the detection-to-treatment pathway. Barriers to effective screening and treatment include system-level factors, such as insufficient integration of mental health resources in cardiology, and patient-related factors like stigma and low acceptance of mental health treatment. Innovative interventions that address these barriers and involve patients as active partners in depression care should be developed through a theory-driven, transparent, multistage process involving key stakeholders such as patients, nurses, and cardiologists. A sound methodological evaluation of such multilevel interventions could answer the question of whether early detection of depression in patients with coronary heart disease would lead to health benefits.